The current state of parent feeding behavior, child eating behavior, and nutrition intake in young children with type 1 diabetes - Mackey, Eleanor R.; Rose, Meredith; Tully, Carrie; Monaghan, Maureen; Hamburger, Samantha; Herrera, Nicole; Streisand, Randi (Pediatric diabetes, 2020)
Background One integral component of type 1 diabetes (T1D) management is attention to nutrition, which can be particularly challenging in young children. Objective The current study reports on parent and child eating/feeding behavior and nutrition intake as compared with current recommendations for pediatric T1D. Subjects Participants were 46 children ages 2 to 5 diagnosed with T1D and one parent. Methods The Behavioral Pediatrics Feeding Assessment Scale (BPFAS) was used to assess parent feeding and child eating behaviors. The Remote Food Photography Method (RFPM) was used to analyze nutrition intake at breakfast. Demographic and medical information were collected via self‐report and medical chart review. Results In the current sample, 37% of BPFAS scores were above the cutoff for problem child eating behavior. Only 28% of participants met the recommended goals for glycemic control (hemoglobin A1c, HbA1c < 7.5). Children who did not meet glycemic control targets reported higher carbohydrate intake than those meeting targets. Protein recommendations were met by 46%; 22.7% met the recommendation for carbohydrate intake, and 45.5% met fat intake recommendations. The majority of the sample did not meet body mass index percentile (BMI%) recommendations with 51% having a BMI% above the 85th percentile. Conclusions Many parents of young children with T1D report problem child eating behaviors. Further, a significant number of young children are not meeting glycemic, nutritional, or BMI guidelines for T1D. Routine screening for dietary difficulties in young children is warranted. Future research should aim to examine interventions targeting families with young children not meeting nutrition, glycemic, or BMI guidelines.